THE EFFECT OF JOB TRAINING, CAREER DEVELOPMENT, AND JOB ROTATION ON EMPLOYEE PERFORMANCE (Survey on Augusta Pelabuhan Ratu Hotel Employees) - Mutiara Regina Agustiana; Faizal Mulia Z; Kokom Komariyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research investigates the impact of job training, career development, and job rotation on employee performance at the Augusta Pelabuhan Ratu Hotel. The study employs quantitative methods, analyzing data collected from 40 employees. The findings indicate that while career development has a significant positive effect on employee performance, job training and job rotation do not have a significant individual impact. However, the combined effect of all three variables shows a statistically significant influence on employee performance, suggesting that a holistic approach to human resource development is crucial for improving overall employee effectiveness in the hospitality sector.